Irreversible Electroporation in Clinical Practice (Springer International Publishing, 2018)
This book provides a comprehensive overview of the clinical use of irreversible electroporation (IRE) - better known by its commercial name, NanoKnife - which is one of the most exciting new needle-guided cancer treatments. The coverage includes the history of IRE, general technique, preclinical research, applications in clinical practice and early clinical results, and future perspectives. Contraindications, treatment planning, potential complications, follow-up imaging, and other practical aspects are fully discussed, with highlighting of useful tips and tricks. Through the delivery of short but highly intense electrical pulses, IRE results in tumor cell membrane permeabilization, causing cells to go into apoptosis. The minimally invasive nature of IRE, combined with the prospect of completely eradicating tumors while preserving delicate structures in the ablation zone, makes IRE the object of worldwide clinical research. This book will be of value for practitioners and trainees in interventional and diagnostic radiology, surgery, medical oncology, HPB and gastroenterology, urology, and radiation oncology.